PHYSICAL AND MECHANICAL PROPERTIES OF BLACK WOOD (EBONY) AS A CONSTRUCTION MATERIAL - Yoresta, Fengky Satria (Department of Architecture, Universitas Tanjungpura, 2015)
This research is aimed to determine physical and mechanical properties of Ebony wood as a construction material. The physical and mechanical properties test is conducted based on ASTM D 143-94 code. The mean value of moisture content and specific gravity of Ebony wood is obtained 12,90% and 0,92 gr.cm-3 respectively. Meanwhile MOE, bending strength, compressive strength parallel to grain, shear strength, and tensile strength parallel to grain are 180.425,87 kg.cm-2; 1656,22 kg.cm-2; 861,55 kg.cm-2; 119,61 kg.cm-2; dan 2.319,03 kg.cm-2 respectively. Based on the test results, it can be concluded that Ebony wood is classified to Strength Class I due to PKKI 1961, so it can be recommended for use in heavy construction such as bridge and building structures Penelitian ini bertujuan menentukan sifat fisis dan mekanis kayu Ebony sebagai material konstruksi. Pengujian sifat fisis dan mekanis dilakukan berdasarkan standar ASTM D 143-94. -3Nilai kadar air rata-rata kayu Ebony diperoleh sebesar 12,90% dan berat jenis 0,92 gr.cm . Sementara nilai rata-rata MOE, kuat lentur, kuat tekan sejajar serat, kuat geser, dan kuat tarik -2 -2 -2sejajar serat berturut-turut adalah 180.425,87 kg.cm ; 1656,22 kg.cm ; 861,55 kg.cm ; -2 -2119,61 kg.cm ; dan 2.319,03 kg.cm . Berdasarkan hasil penelitian dapat disimpulkan bahwa kayu Ebony tergolong kelas kuat I menurut PKKI 1961, sehingga dapat direkomendasikan untuk digunakan pada konstruksi-konstruksi berat seperti jembatan dan struktur bangunan. REFERENCESAghayere A & Jason V. 2007. Structural Wood Design: A Practice-Oriented Approach Using the ASD Method. John Wiley & Sons, Inc., New JerseyBoen T. 2009. Constructing Seismic Resistant Masonry Houses in Indonesia. United Nation.Chauf KA. 2005. Karakteristik Mekanik Kayu Kamper sebagai Bahan Konstruksi. Majalah Ilmiah MEKTEK . Vol 7 : 41-47.Dolan JD. 2004. Timber Structures. Pp 628-669 in Wai FC & Eric ML (Eds) Handbook of Structural Engineering – 2nd ed. USA. Duggal SK. 2008. Building Materials – 3rd ed. New Age International (P) Ltd, New Delhi.Kim NT, Matsumura J & Oda K. 2011. Effect of growing site on the fundamental wood properties of natural hybrid clones of Acacia in Vietnam. Wood Science 57: 87–93.Lempang M & Muhammad A. 2008. Anatomical Structure, Physical and Mechanical Properties of Kumea Batu Wood. Jurnal Penelitian Hasil Hutan. Vol.26(2): 138-147 (In Indonesian)Martawijaya A., Kartasujana I, Mandang YI, Prawira SA, & Kadir K. 2005. Atlas Kayu Indonesia, Jilid II. Departemen Kehutanan, Badan Penelitian dan Pengembangan Kehutanan, Bogor.PKKI (Peraturan Konstruksi Kayu Indonesia). 1961. PKKI NI – 5 1961. Direktorat Jenderal Cipta Karya Departemen Pekerjaan Umum, Bandung.Wanneng PX, Ozarska B, & Daian MS. 2014. Physical Properties Of Tectona Grandis Grown In Laos. Journal of Tropical Forest Science 26(3): 389–396Winandy JE. 1994. Wood Properties. Hal 549-561 dalam Arntzen, Charles J., (Editor) Encyclopedia of Agricultural Science. Vol. 4. October 1994. Academic Press, Orlando.Wood Handbook. 2010. Wood as Engineering Material. Forest Product Laboratory. United States Department of Agriculture Forest Service, Madison.Yancey CW. et al. 1998. A Summary of the Structural Performance of Single Family Wood Framed Housing, Building and Fire Research Laboratory, National Institute of Standards and Technology, Gaithersburg, MD.